Study on momentum interpolation methods with curvilinear collocated grids in single-phase and two-phase flows - Bu, Lin (2013)
To avoid checkerboard pressure in numerical simulations by using collocated grids, the momentum interpolation method was initially proposed by Rhie and Chow and subsequently revised by various researchers. All the momentum interpolation methods are classified into two categories, which are called method A and method B in this article. The performance of the two kinds of methods is evaluated for both single- and two-phase flow in the present work. It is found that method B is more robust for the numerical simulation of two-phase flow.